1998
DOI: 10.1007/s005350050066
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte growth factor accelerates restitution of intestinal epithelial cells

Abstract: Many cytokines are involved in the repair of damaged tissue, and one of these, hepatocyte growth factor (HGF), is involved not only with liver regeneration but also in the repair of other tissues. To investigate the importance of HGF in the repair of the small intestine, we evaluated its effect and that of other growth factors in IEC-6 cells, an intestinal epithelial cell line derived from normal rat small intestine. Round "wounds" were made in confluent monolayers of IEC-6 by silicon rubber-tipped steel rods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 19 publications
0
18
0
1
Order By: Relevance
“…Methotrexate exerts its toxicity by directly inhibiting DNA synthesis, leading to a reduction of mitosis in the crypts and shortening of the villi (Trier, 1962;Altmann, 1974), followed by proliferative recovery phase after the damage (Taminiau et al, 1980). Previous in vivo studies have demonstrated that HGF plays an important role in gastric ulcer repair, and in vitro studies have shown that HGF stimulates intestinal cell proliferation and restitution (Kinoshita et al, 1997;Goke et al, 1998;Nishimura et al, 1998). Despite these reports, limited in vivo studies have been undertaken to investigate the role of HGF in intestinal growth and repair (Kato et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Methotrexate exerts its toxicity by directly inhibiting DNA synthesis, leading to a reduction of mitosis in the crypts and shortening of the villi (Trier, 1962;Altmann, 1974), followed by proliferative recovery phase after the damage (Taminiau et al, 1980). Previous in vivo studies have demonstrated that HGF plays an important role in gastric ulcer repair, and in vitro studies have shown that HGF stimulates intestinal cell proliferation and restitution (Kinoshita et al, 1997;Goke et al, 1998;Nishimura et al, 1998). Despite these reports, limited in vivo studies have been undertaken to investigate the role of HGF in intestinal growth and repair (Kato et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have described increased serum HGF levels in animals with experimental colitis (Dignass et al, 1994;Takahashi et al, 1995b;Matsuo et al, 1997;Nishimura et al, 1998;Ortega-Cava et al, 2002). In the present study, c-Met tyrosine phosphorylation was also observed in colonic tissue of rats with DSS-induced colitis in the absence of HGF treatment, suggesting that endogenous rat HGF was also induced.…”
Section: Hgf Facilitates Mucosal Repair In Dss-induced Colitis 149mentioning
confidence: 98%
“…HGF activator (HGFA) and HGF activator inhibitor type-1, HGF-associated molecules involved in the activation of HGF in injured tissues, are associated with colonic mucosal repair (Itoh et al, 2000;Kataoka et al, 2000b). Additionally, HGF expression was reported to be up-regulated in inflamed colonic mucosal tissue in patients with ulcerative colitis , and plasma HGF levels are increased in animal models of acute colitis (Dignass et al, 1994;Takahashi et al, 1995b;Matsuo et al, 1997;Nishimura et al, 1998;Ortega-Cava et al, 2002). Recombinant human HGF will soon be available for administration to patients with severe liver disease.…”
mentioning
confidence: 99%
“…Moreover, previous studies demonstrated that HGF/SF can stimulate both esophageal and gastrointestinal epithelial growth in primary cultures (Fukamachi et al, 1994;Takahashi et al, 1995). HGF/SF was also shown to enhance both intestinal mucosal repair and function in vivo (Kato et al, 1997a(Kato et al, , 1997bNishimura et al, 1998). Furthermore, it was shown recently that HGF/SF stimulated gastrointestinal tyrosine kinase activity, which colocalizes with c-Met in the brush border membrane of enterocytes (Sunitha et al, 1999 Recently, we described some of the consequences of inappropriate expression of HGF/SF using transgenic mice in which expression of a mouse HGF/SF cDNA was regulated by the mouse metallothionein (MT) gene promoter and 5'/3' genomic flanking sequences as a model system.…”
mentioning
confidence: 97%